A study of occurrence of non-alcoholic steatohepatitis in children with obesity and overweight - Patil, Sharanagouda; Angadi, Kumar; Somasundara, Meghana (Indian Journal of Child Health, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and its increasing prevalence is associated with a concomitant rise in obesity. Anthropometric measurements and non-invasive tests (liver function tests and USG abdomen) help in early recognition of non-alcoholic steatohepatitis (NASH) and reduce consequent morbidity and mortality. Aim: This study aims to study the occurrence of NASH in obese and overweight children and to derive the correlation of NASH with clinical and biochemical parameters in overweight and obese children. Methods: This hospital-based prospective study included children (age ?18 years) who met the inclusion criteria. Diagnosis of NASH was based on the USG abdomen. Measurements included anthropometry, ultrasonography, fasting glucose, alanine aminotransferase (ALT), lipid profile and additional parameters of blood pressure, fasting insulin, and homeostatic model assessment of insulin resistance (HOMA-IR). The variables were compared between children with and without NASH. Results: A total of 146 patients (female: 51.4%, male: 48.6%) were enrolled in the study. The most common age group affected was 11–18 years (50.7%) followed by 6–10 years (43.2%) and <5 years (6.2%). The occurrence of NASH in the study group was 63% of obese and overweight children. Mean weight, body mass index (BMI), waist circumference, waist-hip ratio, blood pressure (BP), serum glutamic-pyruvic transaminase (SGPT), fasting insulin level, and HOMA-IR were significantly higher in children with NASH. There was a significant association between SGPT and NASH. Elevated SGPT of 79.3% and 1.9% were observed among the subjects with and without NASH, respectively. Conclusion: Anthropometric indices and biochemical parameters were more elevated in the NASH group showing its direct correlation with hepatic steatosis.